(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article examines the role of peer feedback as an effective pedagogical tool for improving students’ speaking performance in English as a Foreign Language (EFL) classrooms. The study aims to explore how structured peer feedback influences learners’ fluency, accuracy, and speaking confidence. The study concludes that peer feedback, when properly guided, should be integrated into communicative language teaching practices.